2023
DOI: 10.34133/research.0162
|View full text |Cite
|
Sign up to set email alerts
|

OIP5 Interacts with NCK2 to Mediate Human Spermatogonial Stem Cell Self-Renewal and Apoptosis through Cell Cyclins and Cycle Progression and Its Abnormality Is Correlated with Male Infertility

Abstract: Spermatogonial stem cells (SSCs) have important applications in both reproduction and regenerative medicine. Nevertheless, specific genes and signaling transduction pathways in mediating fate decisions of human SSCs remain elusive. Here, we have demonstrated for the first time that OIP5 (Opa interacting protein 5) controlled the self-renewal and apoptosis of human SSCs. RNA sequencing identified that NCK2 was a target for OIP5 in human SSCs, and interestingly, OIP5 could interact with NCK2 as shown by Co-IP (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…We have recently demonstrated that OIP5 mediates the proliferation and apoptosis of human SSCs via interacting with NCK2. 8 However, the functions and mechanisms of key genes in controlling the proliferation and apoptosis of human SSCs remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that OIP5 mediates the proliferation and apoptosis of human SSCs via interacting with NCK2. 8 However, the functions and mechanisms of key genes in controlling the proliferation and apoptosis of human SSCs remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%